Hands-On Artificial Intelligence for Beginners : an Introduction to AI Concepts, Algorithms, and Their Implementation. - Smith, Patrick D. (Packt Publishing Ltd, 2018)
This book will empower you to apply Artificial Intelligence techniques to design applications for natural language processing, robotics, and other real-world use-cases. You will be able to develop, debug, deploy and optimize intelligent AI systems for self-driving cars, game playing, and much more.